2007
DOI: 10.1063/1.2713238
|View full text |Cite
|
Sign up to set email alerts
|

Microcantilever mechanics in flowing viscous fluids

Abstract: Microcantilevers are often deployed in flowing fluids to measure local flow velocities or to detect rapidly the nanomechanical binding of trace quantities of target analytes. The authors investigate the flow-induced mechanics of microcantilevers by deriving a semianalytical theoretical model for the nanoscale deflections of an elastic microcantilever due to a laminar viscous flow incident upon it. Conversely, the model allows for the estimation of the local flow velocities based on measured microcantilever def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…As a result, a mass resolution in the picogram range was achieved [4], which outperformed the thermogravimetric approaches by five orders of magnitude. Cantilevers shorter than 10 μm in length with sub-attogram sensitivity were demonstrated in 2004 [5-7], enabling the detection of single virus particles of femtogram mass [8].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a mass resolution in the picogram range was achieved [4], which outperformed the thermogravimetric approaches by five orders of magnitude. Cantilevers shorter than 10 μm in length with sub-attogram sensitivity were demonstrated in 2004 [5-7], enabling the detection of single virus particles of femtogram mass [8].…”
Section: Introductionmentioning
confidence: 99%
“…The partial replacement of expensive short fibres by cheap particulates reduces the cost as well as anisotropy. The addition of particulates also helps in keeping the fibres apart, which improves mechanical properties [4,5]. Friend et al observed that the partial replacement of Saffil short fibres by SiC particulates in 7039 Al alloy-based hybrid MMCs did not affect the strength and elastic moduli but improved fracture toughness [6].…”
Section: Introductionmentioning
confidence: 99%
“…2, the cantilever bending deflection is steady state with fluctuation of <<1 nm, which is comparable to the thermal noise predicted as Δz th =(k B T/γ) 1/2 ≈0.03 nm, where k B is the Boltzmann's constant, T is the absolute temperature, and γ is a force constant for a cantilever. It is also noted that when a solution is injected, the fluctuation of a cantilever bending deflection is ∼1 nm, which is attributed to fluid flow that can also drive the fluctuation [37]. The injection of DI water that possesses pH 10.8 induces the upward bending deflection of a microcantilever, which is consistent with our anticipation that a buffer solution with its pH of 10.8 permits the i-motif DNA to be in R form resulting in the bending deflection change of a cantilever.…”
mentioning
confidence: 94%